Statistical Analysis of Macro-Elements Contents of Vitis vinifera (Raisin) Samples Available in Pakistan - Mahmud, Tariq; Rehman, Rabia; Shahid, Aqsa; Usman Alvi, Muhammad (Asian Journal of Chemistry, 2015)
Vitis vinifera (Raisins) are sweet, tasty and nutritious and people have been enjoying them from the very beginning of civilization. They are the most favorite food not only because of its taste but also due to its high micronutrient contents, highest concentration of total phenolic compounds, highest antioxidant activity among the solid food products and rich source of minerals including potassium, magnesium, calcium, iron, sodium, chromium, manganese, nickel and vitamins. Minerals are necessary for the proper functioning of our body. Deficiency of essential minerals can cause various diseases. So, proper intake of these essential minerals is the warranty of good health. In the present study, different samples of various varieties of raisin were collected from local markets and their mineral profile analysis was done. The results obtained were then compared with the values provided by USDA (United States Department of Agriculture). On the average, every 100 g of raisin produced in Pakistan contains 21.5 mg of Na+, 673.5 mg of K+, 63.75 mg of Ca2+, 31.87 mg of Mg2+ and 1.36 mg of Fe2+. The results of this analysis reflect that raisins are considered to be a healthy food and a potential source of important minerals which can efficiently meet the dietary requirements of human beings.